UTILIZAÇÃO DA RAIZ DA YACON NA FORMULAÇÃO DE PÃES SEM GLÚTEN PARA ENRIQUECIMENTO DA DIETA DE CELÍACOS - Schöffer, Jéssie d. N.; Klajn, Vera M.; Büttenbender, Pedro L.; Rosso, Ana C.; Poll, Raysa; Kinalski, Tenisa (Salão do Conhecimento, 2013)
Resumo